2009
DOI: 10.1002/cncr.24496
|View full text |Cite
|
Sign up to set email alerts
|

Mental status changes after hematopoietic stem cell transplantation

Abstract: BACKGROUND:The growing numbers of survivors of innovative cancer treatments, such as hematopoietic stem cell transplantation (HSCT), often report subsequent cognitive difficulties. The objective of this study was to evaluate and compare neurocognitive changes in patients with chronic myelogenous leukemia (CML) or primary myelodysplastic syndrome (MDS) after allogeneic HSCT or other therapies. METHODS: In this prospective cohort study, serial evaluations of attention, concentration, memory, mood, and quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 73 publications
2
37
0
2
Order By: Relevance
“…Most adult survivors recover cognitive function within one year but mild impairments remain evident 5 years post-transplant for some survivors (59, 75, 76). Patient-reported problems are typically discrepant with and higher than detected with objective neuropsychological test results.…”
Section: Resultsmentioning
confidence: 99%
“…Most adult survivors recover cognitive function within one year but mild impairments remain evident 5 years post-transplant for some survivors (59, 75, 76). Patient-reported problems are typically discrepant with and higher than detected with objective neuropsychological test results.…”
Section: Resultsmentioning
confidence: 99%
“…Studies addressing neuropsychological functioning in patients undergoing HSCT reported that 20–40% had cognitive dysfunction involving graphomotor speed, executive and memory abilities prior to transplant (Andrykowski et al, 1992; Chang et al, 2009; Friedman et al, 2009; Harder et al, 2005, 2006; Jacobs et al, 2007; Meyers et al, 1994; Schulz-Kindermann et al, 2007). Several prospective studies documented cognitive decline in the initial months after HSCT (Ahles et al, 1996; Booth-Jones et al, 2005; Friedman et al, 2009; Syrjala et al, 2004; Schulz-Kindermann et al, 2007), but the absence of a decline was also described (Harder et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several prospective studies documented cognitive decline in the initial months after HSCT (Ahles et al, 1996; Booth-Jones et al, 2005; Friedman et al, 2009; Syrjala et al, 2004; Schulz-Kindermann et al, 2007), but the absence of a decline was also described (Harder et al, 2007). At approximately one year post-transplant, cognitive functions were reported to return to or surpass pre-transplant levels in several studies (Chang et al, 2009; Harder et at., 2006; Jacobs et al, 2007; Syrjala et al, 2004; Wenz et al, 2000), but subgroups of patients had persistent impairment or decline on some cognitive domains (Jacobs et al, 2007; Meyers et al, 1994; Syrjala et al, 2004). Syrjala and colleagues (2011) reported further improvement in information processing speed and executive functions, but not in memory or motor dexterity in a large cohort of patients evaluated five years following allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Research that has assessed patients 6 months or longer post-HCT indicates some recovery of cognitive function after acute deficits. [7][8][9][11][12][13][14][15] However, to our knowledge, no prospective studies have followed HCT patients beyond 2 years after transplantation.…”
Section: Introductionmentioning
confidence: 99%